Benthic foraminifera as indicators of relative sea-level fluctuations: Paleoenvironmental and paleoclimatic reconstruction of a Holocene marine succession (Calabria, south-eastern Tyrrhenian Sea). (22nd May 2017) - Cosentino, C.; Molisso, F.; Scopelliti, G.; Caruso, A.; Insinga, D.D.; Lubritto, C.; Pepe, F.; Sacchi, M.
Abstract: This study presents the results of an integrated stratigraphic analysis conducted on a marine gravity core (MSK-12 C4) recovered from the outer continental shelf (82 m water depth) of western Calabria, ∼2.6 km, NE of Capo Vaticano (Eastern Tyrrhenian margin). The gravity core MSK-12 C4 recovered a stratigraphic succession of 4.18 m beneath the seafloor representing the last ∼11.1 ka. Sedimentological analysis, micropaleontological quantitative analysis on benthic foraminiferal assemblages, tephrostratigraphy, sequence stratigraphic analysis of high resolution reflection seismic data recorded in the core site area and AMS 14 C absolute age determinations allowed reconstructing the marine record of the eastern Tyrrhenian margin. Major results of the research work include the progressive sea level rise that controlled the evolution of the western shelf of Calabria during the Holocene and the identification of significant paleoenvironmental and paleoclimatic events. First, a short-lived period (10.6–9.4 ka BP) characterized by a significant increase river discharge seems to reflect a major rainfall during the earliest onset of the Holocene climatic warming. Second, the occurrence of a stratigraphic gap from 8.4 to 5 ka BP possibly the result of non-deposition and/or erosion due to bottom currents. The latter should follow from a major reorganization of the deep water currents system that accompanied the climax of the Holocene warming (Holocene climatic optimum). Third, the micropaleontological evidence of the Little Ice Age (LIA) that, on the basis of the chronology adopted in this study, can be constrained between ∼1600 AD and ∼1850 AD.